STANDARDISASI INSTRUMEN INTEGRITAS AKADEMIK MELALUI PENDEKATAN CONFIRMATORY FACTOR ANALYSIS DAN RASCH MODEL - Asdar, Ahsanul Khair; Bambang Afriadi; Muawanah (Jurnal Manajemen Pendidikan, 2022)
This research was survey research with a quantitative approach that aimed to standardized the academic integrity instruments through the Confirmatory Factor Analysis (CFA) and Rasch Model approaches. The population in this study were all students in universities in Indonesia. The sample used in the study was 452 students (230 students on the first stage and 222 students on the second stage) who were selected using cluster random sampling techniques. The data obtained were analyzed using Gregory analysis (two experts) to obtain the content validity coefficient, factor analysis using the CFA approach, and the Rasch Model. The results showed that the content validity coefficient of the academic integrity instrument was 0,822 (45 items). The results of the CFA analysis according to the first stage trial showed the value of Construct Reliability (CR) and Variance Extracted (VE) for the measurement model was 0,811 and 0,125, while the value of CR and VE for the structural model ​​was 0,940 and 0,763 (six items dropped). The Rasch Model analysis showed one infit item. The results of the CFA analysis according to the second stage trial showed the value of CR and VE for the measurement model was 0,879 and 0,247, while the value of CR and VE for the structural model was 0,950 and 0,918 (one item dropped). The Rasch Model analysis showed all the remaining items in the fit category. The standardized academic integrity instrument consists of 37 statements with dimensions of honesty, trust, fairness, respect, and responsibility.